REVIEW OF ISLAMIC CRIMINAL LAW ON THE ABUSE OF KOMIX COUGH MEDICINE (CASE STUDY OF TELUK PAYO VILLAGE) - Saputra, Mansyur Saputra; Yusida Fitriyati; Muhamad Sadi Is (Tazir, 2025)
The abuse of illegal drugs is a serious challenge faced by the Indonesian people, including the abuse of Komix cough medicine containing dextromethorphan. The absence of laws regulating the prohibition of consuming and selling komix cough medicine, as well as the lack of public understanding of the classification of narcotics, leads to the erroneous assumption that only substances such as shabu, marijuana, and ecstasy are included in narcotics, so this phenomenon is interesting to review in Islamic criminal law. This study aims to identify the factors of Komix cough medicine abuse in Teluk Payo Village and review the case from the perspective of Islamic criminal law. This research is an empirical juridical research that manages and analyzes qualitative data obtained from interviews and literature studies, then the data is described in a qualitative descriptive manner so as to obtain conclusions that can be understood by the reader. The results of the study showed that Komix abuse was influenced by internal factors (personality and family) as well as external factors (environment and association). From the perspective of Islamic criminal law, the use of Komix for intoxicating purposes is equated with khamr which is prohibited because it can damage reason and health, so that the perpetrator can be subject to hudud sanctions in the form of dera.